Alman Hukukunda Elektronik Tapu Sicilinin Gelişimi ve Oluşumu - (:unkn) unknown (My University, 2018)
İlgili makale öncelikle Alman hukukunda elektronik tapu sicil kavramının ortaya çıkışı ve tarihigelişimi ile ilgili bilgi vermektedir. Ayrıca elektronik tapu sicil kavramını Alman hukuku mevzuatıaçısından değerlendirilmekte ve elektronik tapu sicilinin oluşumu ile ilgili olarak takip edilen usul veesasları incelenmektedir. Bu çerçevede, tapu sicilinin aleniyeti ilkesi ve kişilik hakları kapsamında özelhayatın gizliliği uyarınca menfaat dengesinin, elektronik tapu sicili düzenlemesi bakımından ne şekildeele alındığı ortaya konmakta ve son olarak da Türk hukukundaki durum açısından karşılaştırmalı birdeğerlendirme yapılmaktadır.

The article demonstrates the historical development of electronic land register in German law and thoroughly analyses the notion of electronic land register according to German legislation. Furthermore, the article explains the basic rules and principles, regarding the formation of an electronic land register within German law. Moreover, the conflict between the principle of publicity and the right to privacy or more specifically the right to self-determination in relation to electronic land register is discussed and the German legal approach to this conflict of interest is examined. Finally, the legal situation on electronic land register in Turkish law is generally evaluated in comparison to German law.
The Development and Formation of Electronic Land Register in German Law
Keywords: Hukuk